The influence of ethical leadership, organizational justice, and work engagement on teacher loyalty - Komala Hidayatun Najiyah; Ahmad Suriansyah; Ngadimun Ngadimun (Universitas Pendidikan Indonesia, 2025)
Teacher loyalty is a crucial aspect in maintaining the stability and effectiveness of education in primary schools, as reflected in teachers' willingness to work consistently, their reluctance to easily change workplaces, and their positive attitude towards school policies. This study was motivated by the importance of creating a fair work environment and fostering ethical leadership to increase teachers' emotional and professional engagement. This study was conducted to describe and analyze the influence of ethical leadership, organizational justice, and work engagement on the loyalty of SDN teachers in West Pulaulaut Subdistrict. The research method used is a correlational method with a quantitative approach analyzed using path analysis within the framework of Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The sample consisted of 90 teachers, selected through a total sampling technique. The results showed that organizational justice and work engagement have a significant direct effect on teacher loyalty. In contrast, ethical leadership has no direct effect but an indirect effect through work engagement. The findings confirm the important role of justice and work engagement in shaping teacher loyalty, as well as the strategic position of ethical leadership as a factor that supports engagement. Abstrak Loyalitas guru merupakan aspek penting dalam menjaga stabilitas dan efektivitas pendidikan di sekolah dasar yang tercermin dari kesediaan guru untuk bekerja secara konsisten, tidak mudah berpindah tempat kerja, serta menunjukkan sikap positif terhadap kebijakan sekolah. Penelitian ini dilatarbelakangi oleh pentingnya menciptakan iklim kerja yang adil dan kepemimpinan yang etis agar guru lebih terlibat secara emosional dan profesional. Penelitian ini dilakukan untuk menggambarkan dan menganalisis pengaruh kepemimpinan etis, keadilan organisasi, dan keterlibatan kerja terhadap loyalitas guru SDN di Kecamatan Pulaulaut Barat. Metode penelitian yang digunakan adalah metode korelasional dengan pendekatan kuantitatif yang dianalisis menggunakan path analysis dalam kerangka Structural Equation Modeling berbasis Partial Least Squares (SEM-PLS). Sampel berjumlah 90 orang guru yang ditentukan melalui teknik total sampling. Hasil penelitian menunjukkan bahwa keadilan organisasi dan keterlibatan kerja memiliki pengaruh langsung signifikan terhadap loyalitas guru, sedangkan kepemimpinan etis tidak berpengaruh langsung tetapi berpengaruh secara tidak langsung melalui keterlibatan kerja. Temuan ini menegaskan pentingnya peran keadilan dan keterlibatan kerja dalam membentuk loyalitas guru, serta posisi strategis kepemimpinan etis sebagai faktor yang mendukung keterlibatan tersebut. Kata Kunci: keadilan organisasi; kepemimpinan etis; keterlibatan kerja; loyalitas guru